Customer Satisfaction Analysis: Factors Enhancing Purchase Decisions in Higher Education Institution - Suparman, Suparman; M, Aras; Qanitah Tasrudin, Tiara; Alverisa Permatasari, Katarina (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
Higher education institutions face numerous obstacles, including severe rivalry. Higher education institutions must innovate to address these difficulties. The primary goal of this study is to investigate and analyze the elements that influence customer satisfaction and purchase decisions in higher education institutions. This research used quantitative methodologies, with questionnaires distributed to 385 students at one of Indonesia's institutions. The data will be processed using path analysis and correlational analysis with SEM-PLS in the SmartPLS software. The study's findings indicate that customer experience had positive and significant impact on customer satisfaction and purchase decisions (p < 0.05). Communication quality and event marketing positively and significant impacts customer experience and purchasing decisions (p < 0.05). Customer satisfaction significantly affects purchasing decisions (p < 0.05). Higher education institutions must focus on the elements that influence consumer satisfaction and purchase decisions. This can be accomplished through excellent quality communication and appealing marketing strategies.